2020
DOI: 10.5395/rde.2020.45.e18
|View full text |Cite
|
Sign up to set email alerts
|

A micro-computed tomographic evaluation of root canal filling with a single gutta-percha cone and calcium silicate sealer

Abstract: Objectives: The purpose of this study was to evaluate the void of root canal filling over time when a calcium silicate sealer was used in the single gutta-percha cone technique. Materials and Methods: Twenty-four J-shaped simulated root canals and twenty-four palatal root canals from extracted human maxillary molars were instrumented with ProFile Ni-Ti rotary instruments up to size 35/0.06 or size 40/0.06, respectively. Half of the canals were filled with Endoseal MTA and the other half were with AH Plus Jet u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 15 publications
(18 reference statements)
2
15
1
Order By: Relevance
“…We showed that the technique was more beneficial to obturate the root canal with less void formation compared to warm vertical compaction. However, in contrast to our study, a considerable number of recent studies have reported that the filling quality of the SC technique was not inferior but instead superior to other techniques, such as warm vertical compaction [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. While reviewing the papers, we recognized that all the studies were performed only using microcomputed tomography (μCT) but did not observe the sectioned tooth specimens using a microscope.…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We showed that the technique was more beneficial to obturate the root canal with less void formation compared to warm vertical compaction. However, in contrast to our study, a considerable number of recent studies have reported that the filling quality of the SC technique was not inferior but instead superior to other techniques, such as warm vertical compaction [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. While reviewing the papers, we recognized that all the studies were performed only using microcomputed tomography (μCT) but did not observe the sectioned tooth specimens using a microscope.…”
Section: Introductioncontrasting
confidence: 99%
“…However, in terms of void formation, a couple of studies, including ours, reported that the SC technique might be inferior to other techniques, such as the core-carrier method or vertical compaction [ 7 , 19 ]. Nevertheless, a significant number of studies showed that the SC technique did not generate more voids compared to other methods, and thus there are still controversies [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Therefore, in the present study, we reproduced the experiment using a newly launched zirconium-oxide-containing premixed calcium silicate sealer (Endoseal TCS) with similar teeth and protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) was carried out to assess the evidence. The risk of bias assessment was adapted from the previous studies [ 28 , 29 , 30 ] ( Table 2 ). The evaluation was based on the description of the following parameters for the quality assessment of study: sample size calculation, samples with similar dimensions, randomisation process, standardisation of instrumentation and obturation procedures, endodontic treatment performed by a single operator, blinding of the observer and statistical analyses carried out.…”
Section: Data Extractionmentioning
confidence: 99%
“…Kim et al (2020) assessed the quality of root canal filling over time of both extracted human teeth and artificial canals using a calcium silicate cement (Endoseal MTA) with the single cone technique in comparison with canals filled with AH Plus cement. Micro-CT (micro-computed tomography) scans performed immediately after filling the canal did not show significant differences in the percentage of vacuum at all levels between the Endoseal MTA and AH Plus groups in the simulated root canals; after four weeks there were no statistically significant differences in any third of the canals, with the exception of the apical third of the group tested with AH plus which showed a greater percentage of voids; although immediately after filling the canals, Endoseal MTA showed a lower percentage of voids compared to AH plus, over time there seems to be no significant differences between the two [32].…”
Section: Root Canal Filling Efficiencymentioning
confidence: 76%